ChemInform Abstract: Access to Novel Imidazo[1, 5‐a]pyrazine Scaffolds by the Combined Use of a Three‐Component Reaction and a Base‐Assisted Intramolecular Cyclization. Issue 49 (9th December 2014) - Attanasi, Orazio A.; Favi, Gianfranco; Giorgi, Gianluca; Majer, Roberta; Perrulli, Francesca Romana; Santeusanio, Stefania
Abstract Application of aliphatic isothiocyanates other than (XX) fails.